2014
DOI: 10.1007/978-3-319-09952-1_3
|View full text |Cite
|
Sign up to set email alerts
|

An Experiment in Automatic Design of Robot Swarms

Abstract: Abstract. We present an experiment in automatic design of robot swarms. For the first time in the swarm robotics literature, we perform an objective comparison of multiple design methods: we compare swarms designed by two automatic methods-AutoMoDe-Vanilla and EvoStickwith swarms manually designed by human experts. AutoMoDe-Vanilla and EvoStick have been previously published and tested on two tasks. To evaluate their generality, in this paper we test them without any modification on five new tasks. Besides con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
0
9
0
7
Order By: Relevance
“…The empirical studies presented in the paper are unprecedented in the domain of the automatic design of control software for robot swarms-they comprise 350 runs with a swarm of 20 robots; a total of five methods are tested on five tasks. This paper is an extended version of Francesca et al (2014b), which was presented at ANTS 2014. The results of Study A were already contained in Francesca et al (2014b), while the ones of Study B are presented here for the first time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical studies presented in the paper are unprecedented in the domain of the automatic design of control software for robot swarms-they comprise 350 runs with a swarm of 20 robots; a total of five methods are tested on five tasks. This paper is an extended version of Francesca et al (2014b), which was presented at ANTS 2014. The results of Study A were already contained in Francesca et al (2014b), while the ones of Study B are presented here for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…This paper is an extended version of Francesca et al (2014b), which was presented at ANTS 2014. The results of Study A were already contained in Francesca et al (2014b), while the ones of Study B are presented here for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Communication can take place using explicit messages [115,116,117,118,119], or implicitly, by sensing the nearby presence and relative position of other robots [106,115,120,121,122,123,124,125,126,127]. Information acquired from nearby robots can be used to implement simple mechanisms of robot avoidance [123], or, more often, to regulate the position and velocity of a robot according to a desired behavior.…”
Section: Direct Communicationmentioning
confidence: 99%
“…Podury and Sukhatme [121] used potential fields to maximize the area covered by a swarm of robots with defined sensing and communication ranges, with the constraint that each robot must stay within communication range of a minimum number of other robots. In [127], the task of maximizing the area covered by a swarm of connected robots is tackled with an automatic design method using probabilistic finite state machines, where parameters of robot controllers are selected with an optimization algorithm.…”
Section: Dispersionmentioning
confidence: 99%
“…Recent experiments have shown that both manual and automated swarm design methodologies significantly benefit from being constrained to a set of possible robot behaviours, as opposed to being open-ended (Francesca et al 2014). Using the ICR framework, we could identify such behaviour sets by studying how different parts of robot control algorithms affect the overall swarm performance.…”
Section: The Icr Framework and Future Workmentioning
confidence: 99%